2011
DOI: 10.1186/1755-7682-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Reversible dilated cardiomyopathy caused by hypothyroidism

Abstract: The association between lack of thyroid hormones and cardiac dysfunction has been well described. We report two new cases of patients with dilated cardiomyopathy (DCM), revealing a periphery hypothyroidism and for whom cardiac function significantly improved after L thyroxin substitutive treatment. Our cases highlight the necessity to perform thyroid function testing to investigate the etiology of non ischemic DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 7 publications
4
27
0
Order By: Relevance
“…Thyroid hormone has a great effect on the heart and vascular system 1). The heart is sensitive to changes in thyroid hormones, and cardiac disorders are commonly associated with both hyper- and hypothyroidism 3)4).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone has a great effect on the heart and vascular system 1). The heart is sensitive to changes in thyroid hormones, and cardiac disorders are commonly associated with both hyper- and hypothyroidism 3)4).…”
Section: Introductionmentioning
confidence: 99%
“…The manifestations of myxoedema and HF improved during therapy with desiccated thyroid. More recently, cases of hypothyroidism and reversible dilated cardiomyopathy have been reported (87,88). Changes in myocardial gene expression (aMHC and phospholamban) were documented by measuring mRNA extracted from endomyocardial biopsy specimens of a hypothyroid patient with dilated cardiomyopathy before and after T 4 replacement therapy (88).…”
Section: Hf and Hypothyroidismmentioning
confidence: 99%
“…It has long been shown that appropriate thyroid hormone replacement can restore LV function and even reverse pericardial effusions caused by hypothyroidism 2 4. Although the merits of treating subclinical hypothyroidism have been debated, Razvi et al 5 recently demonstrated improvement in cardiovascular risk factors and fatigue with L-thyroxine therapy 6…”
Section: Discussionmentioning
confidence: 99%